PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IVA SD NEGERI 018 SINTONG KECAMATAN TANAH PUTIH - Khairani Khairani; Zulkifli Zulkifli; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is backgrounded to back by its low of result study IPS, aim of research to to level it studying result. The subjects of the research was the students class IVA of SDN 018 Sintong in number 24 students. This research is class action research with two cycles, every cycles concist from two times meeting with one time repeating of daily. Data collection instrument to research this is teacher’s observation sheet, student’s observation sheet, result test study. From research data show that result study student to undergo leveling. This matter can to be proofed with the activity data analysiicall- result teacher to cycle I first meeting 66,67% and second meeting to level become 70,83% to cycle II first meeting 79,17% and second meeting to level become 87,5%. Next analysiical result activity data to cycle I first meeting 66,67% and second meeting to level become 75%.To cycle II first meeting 79,17% and second meeting to level become 87,5%. From this research result be obtained result study student to undergo leveling that is average result study student to base skor is 63,75 to level to cycle I become 70,62,with leveling point 10,78%, to level again to sisklus II that 79.79 with leveling point 25,16%. To completing study to base skor is 10 people (41,67%), to level tocycle I become 16 people (66,67%) to level again to cycle II become 22 people (91,67%). With such can to be concluded that if to be applied model type cooperative studying Two Stay Two Stray (TSTS) can to level it result study class student IPS IVA SDN 018 Soil Sintong White.Keywords: The Cooperative Studying Model TSTS’s Model. Result Study IPS.